The Influence of Celebrity Endorser Towards Consumer Interest Usage of Threads App Through Brand Image in Indonesia - Muhammad Rayhan Hasra; Jushermi Jushermi; Rendra Wasnury (Westscience Press, 2024)
This research aims to examine The Influence of Celebrity Endorser towards Consumer Interest Usage of Threads App through Brand Image in Indonesia. The population in this research is Indonesia people that has hear about Thread Apps. The sampling technique in this research used purposive sampling technique and a sample of 118 sample was obtained. The data analysis method used is path analysis. There are 4 hypothesis on this research. The results of this research show 3 hypothesis are accepted, such as celebrity endorser has affect on brand image, brand image has affect on consumer interest, and celebrity endorser has affect on consumer interest through brand image. However, the rejected hypothesis is celebrity endorser has affect directly on consumer interest.